Frontline perspectives on barriers to care for patients with California Medicaid: a qualitative study - Jessica Faiz; Mariah Blegen; Vanessa Nuñez; Daniel Gonzalez; Daniel C. Stokes; Kevin Truong; Gery Ryan; Medell Briggs-Malonson; Katherine L. Kahn (BMC, 2024)
Abstract Background While insurance is integral for accessing healthcare in the US, coverage alone may not ensure access, especially for those publicly insured. Access barriers for Medicaid-insured patients are rooted in social drivers of health, insurance complexities in the setting of managed care plans, and federal- and state-level policies. Elucidating barriers at the health system level may reveal opportunities for sustainable solutions. Methods To understand barriers to ambulatory care access for patients with Medi-Cal (California's Medicaid program) and identify improvement opportunities, we performed a qualitative study using semi-structured interviews of a referred sample of clinicians and administrative staff members experienced with clinical patient encounters and/or completion of referral processes for patients with Medi-Cal (n = 19) at a large academic medical center. The interview guide covered the four process steps to accessing care within the health system: (1) scheduling, (2) referral and authorization, (3) contracting, and (4) the clinical encounter. We transcribed and inductively coded the interviews, then organized themes across the four steps to identify perceptions of barriers to access and improvement opportunities for ambulatory care for patients with Medi-Cal. Results Clinicians and administrative staff members at a large academic medical center revealed barriers to ambulatory care access for Medi-Cal insured patients, including lack of awareness of system-level policy, complexities surrounding insurance contracting, limited resources for social support, and poor dissemination of information to patients. Particularly, interviews revealed how managed Medi-Cal impacts academic health systems through additional time and effort by frontline staff to facilitate patient access compared to fee-for-service Medi-Cal. Interviewees reported that this resulted in patient care delays, suboptimal care coordination, and care fragmentation. Conclusions Our findings highlight gaps in system-level policy, inconsistencies in pursuing insurance authorizations, limited resources for scheduling and social work support, and poor dissemination of information to and between providers and patients, which limit access to care at an academic medical center for Medi-Cal insured patients. Many interviewees additionally shared the moral injury that they experienced as they witnessed patient care delays in the absence of system-level structures to address these barriers. Reform at the state, insurance organization, and institutional levels is necessary to form solutions within Medi-Cal innovation efforts.